A Study of the Benthic Invertebrates community in Dalmage Lake - Middle of Iraq- - J. Jaweir, Haifa; H. M. Al-Seria, Maysoon (Iraqi Journal of Science, 2023)
Benthic invertebrates diversity on the Al-Dalmage the Lake in the middle of Iraq, in addition to the some chemical properties was the aim of the present study, for a period from January to the December 2013. Six stations of the lake were chosen for monthly samples collection. The result revealed that the water temperature ranged from (9-34) ◦C. According to the values of salinity (1.5-14.6) ‰ the lake was classified as Brackish, while the pH values were neutral tends to near alkaline and ranged from (7.2- 9). The study showed that the lake were well oxygenated due to the dissolved oxygen values which ranged from 7-12 mg/l. The lake considered as very hard according to the total hardness values which range from (825-6980) CaCo3 mg/l. A total of 21286 individual of benthic invertebrates were sorted from all study stations, belong to nine taxa, with the dominance of Crustacea, from which 6238 individuals were sorted in a percent of 29% of the total number of benthic invertebrates. It was also noted that there was a Spatially and temporally variation in species distribution، The highest total number of 4360 individuals was recorded in St (2) while the highest total number recorded in April was 2624.Shanon –Weiner index recorded high values for benthic invertebrates diversity ranged from (1.2-3.8) bit/Ind. Jaccard Presence –community of similarity results showed the highest degree of similarity was (96% (, recorded between St.1 and St.2.